2016
DOI: 10.1186/s12885-016-2259-4
|View full text |Cite
|
Sign up to set email alerts
|

TNF-alpha promotes lymphangiogenesis and lymphatic metastasis of gallbladder cancer through the ERK1/2/AP-1/VEGF-D pathway

Abstract: BackgroundTumor necrosis factor-alpha (TNF-α), a key player in cancer-related inflammation, was recently demonstrated to be involved in the lymphatic metastasis of gallbladder cancer (GBC). Vascular endothelial growth factor D (VEGF-D) is a key lymphangiogenic factor that is associated with lymphangiogenesis and lymph node metastasis in GBC. However, whether VEGF-D is involved in TNF-α-induced lymphatic metastasis of GBC remains undetermined.MethodsThe expression of VEGF-D in patient specimens was detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 44 publications
0
33
0
3
Order By: Relevance
“…TNF-α may also upregulate MMPs in oral cancer cells, thereby promoting invasion and metastasis (18). In addition, TNF-α promotes lymphangiogenesis and lymphatic metastasis in gallbladder carcinoma by activating the ERK1/2 or the activator protein-1/vascular endothelial growth factor (VEGF)-D pathway (19). However, there are no previous reports describing the role of TNF-α in colon cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 83%
“…TNF-α may also upregulate MMPs in oral cancer cells, thereby promoting invasion and metastasis (18). In addition, TNF-α promotes lymphangiogenesis and lymphatic metastasis in gallbladder carcinoma by activating the ERK1/2 or the activator protein-1/vascular endothelial growth factor (VEGF)-D pathway (19). However, there are no previous reports describing the role of TNF-α in colon cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 83%
“…Accumulating evidence suggests that proinflammatory cytokines, including TNF‐α, IL‐6, IL‐1α, IL‐1β, and IFN‐γ, play a vital role in modulating autonomous growth signaling, which influences HCC growth and invasion, and TNF‐α is one of the most critical proinflammatory cytokines . TNF‐α plays a vital role in cancer by promoting the aberrant expression of a variety of genes through signaling pathway activation . The proinflammatory cytokine TNF‐α, which is mainly secreted by macrophages, can induce PTTG1 mRNA and protein expression in a dose‐dependent manner in keratinocytes .…”
Section: Discussionmentioning
confidence: 99%
“…7 TNF-α plays a vital role in cancer by promoting the aberrant expression of a variety of genes through signaling pathway activation. 35 The proinflammatory cytokine TNF-α, which is mainly secreted by macrophages, can induce PTTG1 mRNA and protein expression in a dose-dependent manner in keratinocytes. 9 Our study showed that TNF-α was upregulated in both HCC and paracancer tissues compared with normal liver tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Increased C‐C chemokine receptor 7 (CCR7) expression in tumor cells has been reported to be significantly associated with lymph node metastasis in several cancer types . Interestingly, CCR7 has been found to mediate TNF‐α‐induced lymphatic metastasis of gallbladder cancer . C‐C chemokine receptor 7 is a receptor for the chemokine CCL21 and is expressed in various immune cells that migrate to and within lymphoid tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Interestingly, CCR7 has been found to mediate TNF-ainduced lymphatic metastasis of gallbladder cancer. 12,13 C-C chemokine receptor 7 is a receptor for the chemokine CCL21 and is expressed in various immune cells that migrate to and within lymphoid tissues. Chemokine CCL21 is abundantly expressed on fibroblastic reticular cells in lymph node metastasis.…”
Section: Introductionmentioning
confidence: 99%